Christmas and other horrors - Datlow, Ellen; Golden, Christopher; Percy, Benjamin; Katsu, Alma; Dowling, Terry; Mamatas, Nick; Hirshberg, Glen, 1966-; Nix, Garth; Due, Tananarive, 1966-; Kadrey, Richard; Jones, Stephen Graham, 1972-; Bulkin, Nadia; et al. (Titan Books, 2024)
"The winter solstice is celebrated as a time of joy around the world--yet the long nights also conjure a darker tradition of ghouls, hauntings, and visitations. This anthology of all-new stories invites you to huddle around the fire and revel in the unholy, the dangerous, the horrific aspects of a time when families and friends come together--for better and for worse. From the eerie Austrian Schnabelperchten to the skeletal Welsh Mari Lwyd, by way of ravenous golems, uncanny neighbors, and unwelcome visitors, Christmas and Other Horrors captures the heart and horror of the festive season. Because the weather outside is frightful, but the fire inside is hungry..."--Page 4 of cover.